CONSECRATION IN IGBO TRADITIONAL RELIGION: A DEFINITION - Onwurah, Emeka (Journal of Dharma, 1992)
The art of reading and writing was an innovation in Igboland. This we owe to the effects of both the christian missionaries and the colonial government. However prior to this literary innovation, the traditional Igbo society had an unwritten flourishing way of communication. They also had systematized forms of cosmology, philosophies of life that were often enshrined in myths, pithy sayings, proverbs, folk-lores and even in artistic works. But with the advent of culture contacts came the problem of thought patterns- should the traditional world view be thrown overboard in favour of a wholesale assimilation of imported world view that came with literacy ? If yes, then one would be faced with the problem of endurance of traditional values and beliefs even after so many years of culture contacts.